A review on the effects of chemical pre-treatments on physicochemical, sensorial, antioxidant, human health, and microbiological safety of dried fruit / Siti Nurida Kamaruddin and Naemaa Mohamad - Kamaruddin, Siti Nurida; Mohamad, Naemaa (2021)
Dried fruits known as a nutritious snack, a substitute to sweet or salty snacks due to their flavour, nutritional, and health benefits. In producing dried fruit, it generally undergoes a drying process. However, fruit usually will encounter physical and chemical degradation after drying. Chemical pre-treatment is commonly used before the drying process as it helps to inactive enzymes and produce better quality dried fruit. It is of interest to study the effect of chemical pre- treatment on qualities of dried fruits. In this review, an overview of dried fruits in terms of processing, composition and the effect of chemical pre-treatment on physicochemical properties (colour, texture, pH, total soluble solid, titratable acidity, water activity and moisture content), sensory acceptability, antioxidants (vitamin C and total phenol content), human health and microbiological safety have been discussed. Chemical pre-treatment such as citric acid and potassium metabisulfite among the most commonly used pre-treatments. Moreover, chemical pre- treatment helps enhance colour and minimize the shrinkage of dried fruit as compared to untreated one. It also enhances the dried fruit’s acceptability and increases vitamin C, total phenol content and provides microbiological safety of dried fruit. Therefore, chemical pre-treatment before drying is important in producing good quality dried fruits. This research will be beneficial to the food industry which produces dried fruit products as this review provides more information about chemical pre-treatments that are suitable to be applied on their product.